ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETIDAKPATUHAN WAJIB PAJAK (Studi Empiris Pada Pengusaha UMKM Di KPP Pratama Pekanbaru Senapelan) - Yola Febriani Syahputri; Zirman -; Rusli - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of attitudes, subjective norms, moral obligation, perceived behavioral control and knowledge of taxation on the intention to behave noncompliant and noncompliance behavior of taxpayer.This study used purposive random sampling with 100 samples obtained from the calculation formula slovin. Data collection techniques in this study is in the form of a questionnaire, while the data analysis technique used is Partial Least Square (PLS) with SmartPLS software version 2.0. The results showed that the attitude has positive and significant effect on the intention to noncompliant, subjective norm has positive and not significant influence on the intention to noncompliant, moral obligationhas positive and significant effect on the intention to noncompliant, perceived behavioral control has positive and not significant influence on the intention to noncompliant and noncompliance behavior of taxpayers, knowledge of taxation has positive and significant effect on the noncompliance of taxpayer and intentio has positive and significant effect on the noncompliance behavior of taxpayer.Keywords: attitudes, subjective norms, moral obligation, perceived behavioral control, knowledge of taxation, intention, taxpayer noncomliance.